Ontogenetic transition from specialized root hairs to specific root-fungus symbiosis in the dominant Mediterranean seagrass Posidonia oceanica - Borovec, Ondřej; Vohník, Martin (Scientific reports, 2018)
Terrestrial plants typically take up nutrients through roots or mycorrhizae while freshwater plants additionally utilize leaves. Their nutrient uptake may be enhanced by root hairs whose occurrence is often negatively correlated with mycorrhizal colonization. Seagrasses utilize both leaves and roots and often form root hairs, but seem to be devoid of mycorrhizae. The Mediterranean seagrass Posidonia oceanica is an exception: its adults commonly lack root hairs and regularly form a specific association with a single pleosporalean fungus. Here we show that at two sites in the southern Adriatic, all its seedlings possessed abundant root hairs with peculiar morphology (swollen terminal parts) and anatomy (spirally formed cell walls) as apparent adaptations for better attachment to the substrate and increase of breaking strain. Later on, their roots became colonized by dark septate mycelium while root hairs were reduced. In adults, most of terminal fine roots possessed the specific fungal association while root hairs were absent. These observations indicate for the first time that processes regulating transition from root hairs to root fungal colonization exist also in some seagrasses. This ontogenetic shift in root traits may suggests an involvement of the specific root symbiosis in the nutrient uptake by the dominant Mediterranean seagrass.
Keywords: mycelium; symbióza; Mycorrhizae; listy rostlin; kořeny rostlin; Alismatales; Adaptation, Physiological; Ascomycota; Mycelium; Plant Roots; Mediterranean Sea; fyziologická adaptace; Symbiosis; mykorhiza; Středozemní moře; Plant Leaves